Studi Metode Campuran untuk Membingkai Ulang Pembangunan Ekonomi melalui Kesetaraan Gender di Indonesia - Siti Pitriani; Muhammad Ihsan Maulana; Laura Novelia Suhanto (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2026)
This research examines the correlation between Gender Equality and Inclusive Economic Growth. While, analyzes economic policies using liberal feminist theory and the CEDAW normative framework. Liberal feminism emphasizes equal rights and access for women, focuses on women's challenges in formal sector employment and barriers to full economic participation. The research method used is mixed methods by combining qualitative and quantitative methods. Combining qualitative and quantitative methods in the same study is an approach that ensures that data is fully supported, valid, and reliable. The implementation of CEDAW and Liberal Feminism principles has not been fully reflected in existing policies in Indonesia, especially in policies that do not fully focus on gender issues. Based on the results of our research, we provide recommendations in the form of a She-covery Blueprint that aims to optimize the alignment of general-based policies with the principles of CEDAW and Liberal Feminism.